Rethinking power and institutions in the shadows of neoliberalism: (An introduction to a special issue of World Development). (August 2019) - Kashwan, Prakash; MacLean, Lauren M.; García-López, Gustavo A.
Highlights: Neoliberal institutional reforms involve power, not just technical expertise. Our power in institutions matrix highlights multiple dimensions of power in reforms. Neoliberalism creates winners and losers but also produces new distributive politics. Citizen groups wield counter-powers to shape elite-dominated institutional reforms. Access to power is central to institutions for inclusive and sustainable development. Abstract: Despite the recognition that institutions matter for international development, the debates over institutional reforms tend to obscure the role of power. Neoliberal models of development are often promoted in terms of their technical merits and efficiency gains and rarely account for the multiple ways that social, economic and political power shape institutional design and institutional change. Even recent efforts to address power tend to conceptualize it too narrowly. This special issue seeks to rethink the role of power in institutional creation and change in the context of persistent neoliberalism. In the introduction, we synthesize the literature on the nature of power to develop a new conceptual framework – a power in institutions matrix – that highlights the multiple dimensions of power involved in institutional development and change. We argue that such a theoretically-informed mapping of power in institutions will enable scholars, practitioners, and citizen groups to go beyond the standard critiques in order to analyze the multifaceted effects of neoliberal institutional change. Our introduction draws on an extensive literature review as well as the special issue contributors who examine institutional change in a variety of policy sectors in Africa, South Asia, Latin America, and North America. We find that a range of diverse local, national and transnational actors, with disparate access to power, negotiate institutional changes from above and below through overt imposition of and resistance to new rules, influence of agendas, and promotion of discourses. Neoliberalism thus creates a new distributive politics. The special issue thus offers a theoretically-grounded approach for linking international and domestic power differences to the process of institutional change, with a specific focus on equity and sustainability. In a departure from the current literature's focus on elite bargains, we showcase the efforts by less powerful groups to gain a foothold in decision-making processes.